An examination of the effects of capital structure on corporate tax: a case study of Indonesian Stock Exchange consumer goods companies - Anas, Khoiruddin; Susanti, Havi; Supriyadi, Supriyadi (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to ascertain and evaluate if the company's corporate income tax liability is partially and concurrently influenced by its capital structure, specifically by its long-term debt to equity ratio and debt to asset ratio. This kind of quantitative study is done on a pre-selected group or sample. Purposive sampling was used in this study to collect samples, with 56 manufacturing businesses in the consumer products sector listed on the Indonesia Stock Exchange for the 2019–2022 timeframe meeting predefined criteria. Panel data regression analysis was used as the data analysis approach, and Eviews 12 was used. Using the traditional assumption test, T test, F test, and R-Squared test, the Fixed Effect Model (FEM) was the regression model that was employed. The Long Term Debt to Asset Ratio (LDAR) had no impact on the amount of corporate income tax that the firm had to pay, according to the test findings obtained using the t test, which indicated that the initial hypothesis of this study was rejected. The study's second hypothesis, according to which the company's corporate income tax liability is impacted by the Debt to Equity Ratio (DER), is accepted. In the meanwhile, the F test demonstrates that the combined impact of the Long-term Debt to Asset Ratio (LDAR) and Debt to Equity Ratio (DER) on the amount of corporate income tax due.